2019
DOI: 10.9734/ejmp/2019/v29i330155
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Independent Vasorelaxant Effects of Anthocyanins-Enriched Extract from Odontonema strictum (Nees) Kuntze (Acanthaceae) Flowers: Ca2+ Channels Involvement

Abstract: Aims:We aimed in this study to investigate the mechanisms of the vasorelaxation effect caused by the anthocyanins-enriched extract of Odontonema strictum flowers. Study Design: Anthocyanins-enriched extract of Odontonema strictum flowers and vasorelaxantes activities of mice aortic rings. Place and Duration of Study: The flowers of Odontonema strictum (Nees) Kuntze (Acanthaceae) were collected in January 2015 at the "Institut de Recherche en Sciences de la Santé (IRSS)" experimental station in Ouagadougou. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…High Blood Pressure Ribes nigrum C3G, C3R, D3G, D3R ↑eNOS mRNA levels ↑NO synthesis [11] Odontonema strictum ↓CaCl2 and U46619 effect [12] Diabetic Heart Disease Vaccinium vitis-idaea C3G, C-3-Ara, C-3-Gal ↑Antioxidant [13] Oryza sativa C3G ↓TLR4/NFκB ↓active hypertrophy ↓Fibrosis associated molecular marker [14] Oryza sativa C3G ↑Survival signals ↓Apoptosis and the associated proapoptotic proteins [15] Table 1. Cont.…”
Section: Diseases Plant Origin Anthocyanin Types Mechanism Referencementioning
confidence: 99%
See 1 more Smart Citation
“…High Blood Pressure Ribes nigrum C3G, C3R, D3G, D3R ↑eNOS mRNA levels ↑NO synthesis [11] Odontonema strictum ↓CaCl2 and U46619 effect [12] Diabetic Heart Disease Vaccinium vitis-idaea C3G, C-3-Ara, C-3-Gal ↑Antioxidant [13] Oryza sativa C3G ↓TLR4/NFκB ↓active hypertrophy ↓Fibrosis associated molecular marker [14] Oryza sativa C3G ↑Survival signals ↓Apoptosis and the associated proapoptotic proteins [15] Table 1. Cont.…”
Section: Diseases Plant Origin Anthocyanin Types Mechanism Referencementioning
confidence: 99%
“…Black currant extract (BCE) contains high anthocyanins concentrations and increases NO synthesis via endothelial nitric oxide synthase, which are critical regulators of cardiovascular disease [11]. Anthocyanin-enriched extracts of Odontonema strictum flowers can block the contraction of aortic rings because anthocyanin (400 µg/mL) inhibits the effects of CaCl 2 and a thromboxane A 2 analog agonist (U46619) in physiological salt solution [12]. Blood pressure was significantly reduced after consumption of 300 mL of anthocyanin-rich cherry in older adults [73].…”
Section: Vaccinium Asheimentioning
confidence: 99%
“…Odontonema strictum root and stem and Trolox free radical scavenging activity were performed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) [21]. Briefly, after 30 min of incubation in the dark at room temperature, the absorbance of 10 μL of samples and Trolox added to 200 μL of DPPH (0.04 mg/mL) was measured at 490 nm using a Bio-Rad spectrophotometer (model 680, Japan).…”
Section: Dpph• Essay: Hydroethanolic Extracts Ofmentioning
confidence: 99%
“…Due to their potential pharmacological effects and commercial viability, the medicinal properties of plants have been investigated worldwide [25] in light of contemporary scientific breakthroughs. Numerous aromatic and medicinal plants include antioxidant-active chemical compounds (flavonoids, tannins, sterols, triterpenes) [20] [26]. Observations have shown that phenolic compounds inhibit amylase and glucosidase associated with lipid peroxidation, type 2 diabetes, and blood pressure regulation [27].…”
Section: Flavonoids and Tannins Detectionmentioning
confidence: 99%